Ant fauna (Hymenoptera: Formicidae) in Magnoliophyta native to the Atlantic forest - Morini, Maria Santina de C.; Kamazuka, Nancy; Leung, Roberto [UNESP]; Suguituru, Silvia S.; Da Silva, Luciane F. (My University, 2006)
The aim of the study was to analyze the preferences of ant species visiting the trunks of eight species of Magnoliophyta, belonging to the families Fabaceae, Arecaceae, Myrtaceae, Melastomataceae and Euphorbiaceae, located in a fragment of the Atlantic Forest in southeastern Brazil. A total of 101 ant species, belonging to eight subfamilies and 32 genera, were sampled during the 12-month collection period. Close to 30% of the ant species can be considered arboreal, and the others are species that nest in the ground and use trees only for foraging, which can be occasional, as in the case of the Ecitoninae sampled in Arecaceae and Euphorbiaceae. Pachycondyla mesonotalis was the only species collected on all the Magnoliophyta, whereas Camponotus rufipes, Acromyrmex niger and Crematogaster spp., were found on 87.5% of the trees analyzed. No strong similarities were found, using the Jaccard Index, among plant species in the same family of Magnoliophyta based on the visiting ants, except for the Euphorbiaceae species. This result is probably related to the presence of extra-floral nectar, which is very attractive to ants and characteristic of this family.
Keywords: Angiospermae; Ant; Euphorbiaceae; Richness; Serra do Itapety; Acromyrmex niger; Arecaceae; Camponotus rufipes; Ecitoninae; Euphorbia; Fabaceae; Formicidae; Hymenoptera; Magnoliophyta; Melastomataceae; Myrtaceae; Pachycondyla mesonotalis